Improving The Speaking Ability by Using Story Games Technique - Dwi Nur Hadiyansah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
At the university Ibrahimy Sukorejo, the researcher found that many students still get difficulty learning speaking skills in class, especially in the first semester. The lecturer had already done so much direct research but still didn’t find a perfect way in solving the problem for the student. This research was taken at Ibrahimy University Sukorejo and used the Class action research (CAR) Method. To collect the data, the researcher used the value of the test. the researcher directly got in touch with students. The researcher gave the pre-test and post-test to know the student’s speaking ability. The test is taken from an oral test because it measures speaking ability. As shown in the research of the fourth meeting the student’s assessments showed that the student’s speaking proficiency progressed. Many students, who were at level 2 in the previous meeting, could reach level 3 in the last cycle. The amounts were 21 students. The rest were 9 students at level 3+.